2012
DOI: 10.4261/1305-3825.dir.5346-11.1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tumor volume on survival in renal cell carcinoma patients

Abstract: 480R enal cell carcinoma (RCC) constitutes 85% of all primary malignant tumors arising from kidney and nearly 3% of adult cancers (1-6). Approximately 20%-30% of patients diagnosed with RCC have metastasis at the time of diagnosis (1). In patients with recurrent RCC, progression of the disease, the period of survival, and the disease process can be predicted owing to many morphological, clinical, histological, and molecular parameters (3). The prognostic markers of RCC include tumor node metastasis (TNM) stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Seçil et al, measured the radiologic tumor volume (RTV) with the help of a View-Forum workstation that can process 3D images. 17 In another study, RTV was measured with the help of a medical imaging processing system for measurements of volumetric. 18 Choi et al, measured the RTV using Xelis software.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seçil et al, measured the radiologic tumor volume (RTV) with the help of a View-Forum workstation that can process 3D images. 17 In another study, RTV was measured with the help of a medical imaging processing system for measurements of volumetric. 18 Choi et al, measured the RTV using Xelis software.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Seçil et al, reported that when RTV rises, the Fuhrman grade also rises for whole patients. 17 Choi et al, found that RTV correlated with pathologic grade. 9 Our study had some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor volume changes shown in Figure 6 clearly indicate that early treatment (small-size initial tumors) is important to obtain remarkable therapeutic effect [35][36][37]. Therefore, late treatment (largesize initial tumors) may be effective in PDT only with higher drug and light doses.…”
Section: In Vivo Photodynamic Therapeutic Efficacymentioning
confidence: 99%
“…is highly affected by tumor sizes, such as 92.0% for ≤110 cm 3 and 62.2% for >110 cm 3 [35]. William Jr.…”
Section: In Vivo Photodynamic Therapeutic Efficacymentioning
confidence: 99%
See 1 more Smart Citation